What do managers think about the potential of success of CrM campaigns? : managers’ perspective regarding cause-related marketing - Castanheira, Bruna Monteiro (2019)
This research emerged with the intent to analyze Cause-related Marketing from the perspective of companies. The main purpose was to collect, gather and to interpret information regarding this subject, trying to achieve a better understanding about what managers think about CrM: analyzing the level of acceptance and usage of this marketing tool, based on the model UTAUT, used to interpret the collected data. As research method the main adopted method was in-depth interviews, but a brief questionnaire was also provided to the interviewees in order to receive additional information. Even though CrM was well evaluated by the participants and is well positioned in terms of acceptance and usage, based on the four factors analyzed: performance and effort expectancy, social influence and facilitating conditions, this study lead to conclusion that managers see the benefit of company partaken in initiatives as such but not necessarily Cause-related Marketing. Interviewees express excitement towards CrM, but even more for the idea of companies really caring and taking their interest, time and funds to help consumers social concerns, not necessarily in the way of a partnership with a cause but as a way of being of the firm.